The separation of kyanite from quartz by flotation at acidic pH. (June 2016) - Jin, Junxun; Gao, Huimin; Chen, Xumeng; Peng, Yongjun
Highlights: A good separation of kyanite from quartz was achieved at acidic pH. The collector, sodium petroleum sulfonate, only adsorbed on kyanite. Fe 3+ -activated quartz more than kyanite exacerbating the separation. Sodium silicate significantly depressed the flotation of iron-activated quartz. Sodium silicate depressed the flotation of iron-activated kyanite slightly. Abstract: An effective separation of kyanite from quartz by flotation is a challenge due to their similar surface properties and surface activation by metal ions. This study investigated the effect of pH, Fe 3+ and sodium silicate on the separation of kyanite from quartz using anionic collector, sodium petroleum sulfonate (SPS). Zeta potential measurement, infrared spectroscopic analysis and chemical speciation were conducted to identify the underpinning mechanisms. It was found that a good separation of kyanite from quartz was achieved at pH = 4.0 due to the selective adsorption of SPS on kyanite. However, the presence of Fe 3+ altered the electrical property on quartz which became attractive to SPS, enhanced quartz flotation and hence exacerbated the separation of kyanite from quartz. It is interesting that sodium silicate selectively depressed the flotation of iron-activated quartz by covering the activation sites and prohibiting collector adsorption. Although sodium silicate also interacted with kyanite, SPS still adsorbed on kyanite through reacting with Al atoms and therefore the depression of kyanite flotation by sodium silicate in the presence of Fe 3+ was limited.